2019
DOI: 10.1097/gox.0000000000002149
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Wrist Placement for Vascularized Submental Lymph Node Transfer Significantly Improves Breast Cancer–Related Lymphedema

Abstract: Background:Vascularized submental lymph node flap transfer to the wrist is an effective treatment for breast cancer–related lymphedema. Dorsal placement was hypothesized to offer superior outcomes due to favorable venous drainage; however, the flap is more visible in this position compared with the volar side and was a cosmetic concern for patients. This study compared the treatment response of breast cancer–related lymphedema with the placement of vascularized submental lymph node flaps at the wrist, between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…Where heterotopic transfer was indicated, the preferred lymph node flaps were the submental, lateral thoracic, jejunal mesenteric, or right gastroepiploic, using either the radial or ulnar recipient vessels, depending on the distribution of the dermal backflow; dorsal transfer was performed when indicated using the dorsal radial vessels. 38 Localized direct excision of fibroadipose soft tissues, including the typically thickened deep fascia, was performed to provide a pocket for the lymph node flap and to allow tension-free primary skin closure; occasionally, a small temporary skin graft was used to relieve tension that was excised later in the clinic. Where residual obstructed lymphatic channels were identified on indocyanine green lymphography, lymphovenous bypass (LVB) was also performed.…”
Section: Surgical Techniques and Perioperative Managementmentioning
confidence: 99%
“…Where heterotopic transfer was indicated, the preferred lymph node flaps were the submental, lateral thoracic, jejunal mesenteric, or right gastroepiploic, using either the radial or ulnar recipient vessels, depending on the distribution of the dermal backflow; dorsal transfer was performed when indicated using the dorsal radial vessels. 38 Localized direct excision of fibroadipose soft tissues, including the typically thickened deep fascia, was performed to provide a pocket for the lymph node flap and to allow tension-free primary skin closure; occasionally, a small temporary skin graft was used to relieve tension that was excised later in the clinic. Where residual obstructed lymphatic channels were identified on indocyanine green lymphography, lymphovenous bypass (LVB) was also performed.…”
Section: Surgical Techniques and Perioperative Managementmentioning
confidence: 99%
“…For the VGLNT group, there are three recipient sites available for lymph tissue transfer with a lot of controversy in the literature. 29 Despite the axillary area is typically operated previously and irradiated, which makes the dissection of recipient's vessels harder, the release of the scary fibrotic tissue and decompression of the axillary veins could improve the lymphatic obstruction so, we used usually when lymphedema treatment was combined with breast reconstruction using DIEP flap. Distal lymph node flap placement has the benefits of intact healthy recipient vessels and improving distal limb lymph drainage against gravity.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Aljaaly et al also reported on the QoL after VLNT. (30) They found that the general QoL increased significantly with 5.5 points and that all the subdomains scored decreased significantly. Upon subgroup analysis they found that, after 12 months, patients who received a VLNT to the volar side of the wrist instead of the dorsal side had a better score regarding the general QoL and the appearance subdomains (p<0.05).…”
Section: Quality Of Lifementioning
confidence: 96%
“…However, only eight studies reported outcomes of both the healthy and affected extremity, or the decrease in extremity differences compared to the difference prior to surgery. (15,(24)(25)(26)(27)(28)(29)(30) These eight studies were analysed and the results are demonstrated in a forest plot (Figure 2). The mean reduction of the volume difference between the healthy and affected extremities was 40.31% (CI 31.44-49.17).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation